Identification of the agent causing anthracnose on Sansevieria spp., in Costa Rica. - Pérez León, Gerardo (2013)
Sansevieria spp. (Agavaceae), native to Africa and Asia, is a foliage ornamental known as “mother-in-law’s tongue” or sansevieria. S. trifasciata (St) is the species with the highest number of cultivars on the Costa Rican export market. (to the United States and the Netherlands). Leaf samples of S. trifasciata var. “Hahnii” with circular and aqueous lesions, (some dried and elongated) were analyzed. From infected tissue five monohyphal isolates were obtained. The pathogen was identified as Colletotrichum sansevieriae Nakamura (CsN) on the basis of pathogenicity tests, morphology and molecular techniques. Colonies were creamcolored, flat and produced few conidia. The pathogenicity of the isolates was assessed on 7 varieties of St; Sansevieria sp., var. Jiboia; S. cylindrica and the ornamentals Codiaeum variegatum, Cordelyne terminalis and Dracaena deremensis through greenhouse (pot) and laboratory (separate leaves) inoculations. In both conditions disease symptoms were reproduced. Five of the S. trifasciata varieties evaluated developed symptoms, var. “Hahnii” the most susceptible. The same pathogen was reisolated from inoculated leaves (Koch’s postulates). PCR amplification of the ITS region with starters ITS5 and ITS4 yielded a single fragment of approximately 600 base pairs. Sequences of the ITS regions of isolates were identical. Sequences exhibited 99-100% nucleotide identity to isolates of CsN collected from diseased sansevieria in Australia and USA. Phylogenetic analysis, based on ITS2 region, indicates that the Costa Rican isolates clustered (99% bootstrap support) with the type species CsN from Japan and Australia and USA isolates. To our knowledge, this is the first report of CsN causing anthracnose of sansevieria in C.R.